Anchoring of both PKA and 14-3-3 inhibits the Rho-GEF activity of the AKAP-Lbc signaling complex - Diviani, Dario (2004)
A-kinase anchoring proteins (AKAPs) target the cAMP-regulated protein kinase (PKA) to its physiological substrates. We recently identified a novel anchoring protein, called AKAP-Lbc, which functions as a PKA-targeting protein as well as a guanine nucleotide exchange factor (GEF) for RhoA. We demonstrated that AKAP-Lbc Rho-GEF activity is stimulated by the alpha subunit of the heterotrimeric G protein G12. Here, we identified 14-3-3 as a novel regulatory protein interacting with AKAP-Lbc. Elevation of the cellular concentration of cAMP activates the PKA holoenzyme anchored to AKAP-Lbc, which phosphorylates the anchoring protein on the serine 1565. This phosphorylation event induces the recruitment of 14-3-3, which inhibits the Rho-GEF activity of AKAP-Lbc. AKAP-Lbc mutants that fail to interact with PKA or with 14-3-3 show a higher basal Rho-GEF activity as compared to the wild-type protein. This suggests that, under basal conditions, 14-3-3 maintains AKAP-Lbc in an inactive state. Therefore, while it is known that AKAP-Lbc activity can be stimulated by Gα12, in this study we demonstrated that it is inhibited by the anchoring of both PKA and 14-3-3.